Cryptoperla dui, sp. n., a new stonefly from South China (Plecoptera: Peltoperlidae) - Sivec, Ignac (Illiesia, 2005)
Cryptoperla dui, sp. n. is described from male specimens taken in Sichuan, and Yunnan provinces, China. The new species is superficially similar to C. bisaeta (Kawai) and C. kali Stark but may not be phylogenetically close to either.
Keywords: insekti; Plecoptera; vrbnice; China; Cryptoperla